2021
DOI: 10.1111/ceo.13914
|View full text |Cite
|
Sign up to set email alerts
|

Epiretinal membrane: A review

Abstract: The prevalence of epiretinal membrane (ERM) is 7% to 11.8%, with increasing age being the most important risk factor. Although most ERM is idiopathic, common secondary causes include cataract surgery, retinal vascular disease, uveitis and retinal tears. The myofibroblastic pre‐retinal cells are thought to transdifferentiate from glial and retinal pigment epithelial cells that reach the retinal surface via defects in the internal limiting membrane (ILM) or from the vitreous cavity. Grading schemes have evolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
63
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 157 publications
3
63
0
1
Order By: Relevance
“…Increases in macular CSF thickness and blood vessel tortuosity, such as that observed in the dentist group in this study, are also seen in the development of epiretinal membranes (ERMs) [32,33]. However, no other signs of ERMs, such as increased macular reflectance, changes in the topography of the foveal pit, reduced contrast sensitivity, or reduced MPOD, were observed in the present study [32,34,35]. Similarly, although the broader range of MPOD values in the dentist group than in the control group was consistent with a disturbance of macular pigmentation, other evidence of a disruption of macular pigmentation, such as the mottling associated with AMD, was not observed [36].…”
Section: Discussionsupporting
confidence: 40%
“…Increases in macular CSF thickness and blood vessel tortuosity, such as that observed in the dentist group in this study, are also seen in the development of epiretinal membranes (ERMs) [32,33]. However, no other signs of ERMs, such as increased macular reflectance, changes in the topography of the foveal pit, reduced contrast sensitivity, or reduced MPOD, were observed in the present study [32,34,35]. Similarly, although the broader range of MPOD values in the dentist group than in the control group was consistent with a disturbance of macular pigmentation, other evidence of a disruption of macular pigmentation, such as the mottling associated with AMD, was not observed [36].…”
Section: Discussionsupporting
confidence: 40%
“…Fibrosis has been described in diverse retinal diseases and contributes to disease progression 39 (e.g., subretinal fibrosis secondary to AMD 62 or fibrotic epiretinal membranes 63 ). Interestingly, we also observed fibrosis in our AAV-TNF-α driven model, however, in contrast to AMD, we did not observe subretinal fibrosis, but rather the development of a fibrotic epiretinal membrane-like layer in the inner retina.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study observed epiretinal proliferation at the vitreoretinal interface in RVO eyes [29]. Meanwhile, other studies showed that immunity and inflammation in the retina were involved in complications secondary to RVO, such as ERM and retinal atrophy [3,21,[30][31][32]. However, we excluded RVO eyes with ERM in this study in order to reduce the impact on images and MLC count.…”
Section: Discussionmentioning
confidence: 99%